Exploring Factors to enhance Organizational Dissent: What is Moderating Effect of Psychological Safety? - Naz, Saman; Sandhu, Moeed Ahmad; Tufail, Muhammad Sajid (Pakistan Journal of Humanities and Social Sciences, 2024)
The leading objective of this research article is to examine the existing relation between the threat to personal identity, the perception of politics as well as organisational dissent. This study explored mediating role regarding TPI and the moderating effect of psychological safety as well. The research design used for this purpose is cross-sectional .Questionnaires were used for the collection of data by the researcher. The questionnaire was distributed to among 201 respondents using simple random sampling. The gathered data was examined through SPSS and AMOS. The findings of the study revealed that threat to personal identity and perception of politics had significant effect on organizational dissent. Moreover, mediating role of TPI and moderating role of psychological safety was confirmed as well. This research discuss the implication and limitations of the study in details.